Penetrating Ocular Injury Management in Intraocular Foreign Body (IOFB) and Traumatic Cataract - Putri, Nerissa Tamara; Firmansjah, Muhammad; Prastyani, Reni (Folia Medica Indonesiana, 2022)
Highlight: • The management of penetrating ocular injury with IOFB and traumatic cataracts needs a thorough examination of the mechanism of injury, location, size, and composition of IOFB. • Endophthalmitis, retinal detachment, and development of PVR are potentially vision-threatment. Abstract: Most IOFB are metallic and found in males of productive age as a consequence of work-related accidents. A 45-year-old man complained of sudden blurred vision in the left eye (3/60 pinhole 5/12) after getting hit by a foreign body when cutting grass with a lawn mower. Anterior segment examination revealed a 10 mm long, one-plane, straight, full thickness, already sutured inferonasal corneal laceration, inferonasal traumatic iridectomy size 3x7 mm, and opaque lens. Head CT-scan revealed opacity with metallic density intraocularly. Ultrasonography revealed an echogenic lesion, particle-shaped with 100% RCS complex density, located at the inferonasal of the vitreous cavity. Focal laser photocoagulation was performed preoperatively because there was a tear at the superonasal of the retina. The patient underwent cataract extraction, intraocular lens implantation, vitrectomy, and IOFB extraction in a one-step procedure. IOFB was found at the inferonasal side of a vitreous cavity with size 3 x 1 mm, metallic, and not attached to the retina. Silicon oil tamponade was used as a precaution because there were retinal tears. Postoperatively, the left eye's visualacuity was 5/20. After 6 months, the silicon oil was evacuated and the visual acuity became 5/8.5.